Explaining the procyclicality of fiscal policy in developing countries - Håvard Halland; Michael Bleaney (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2011)
The procyclicality of fiscal policy that is prevalent in developing countries and emerging markets is well known. Its explanation is less clear. Recently, social inequality and the combination of corruption and democracy have been suggested as alternatives to the traditional explanation of these countries' exposure to boom-bust cycles in international credit markets. Differences in methodological approach are also partly responsible for diverging empirical results. In this paper, competing hypotheses are tested on a comprehensive set of measures of the cyclicality of fiscal policy. The evidence for corruption and democracy is stronger than for social inequality or net foreign debt, but the interpretation of this result is less obvious, since the index of corruption is closely correlated with poor credit ratings. In OECD countries, by contrast, the cyclicality of fiscal policy largely reflects the strength of automatic stabilizers.
Keywords: 330; fiscal cyclicality; fiscal policy; business cycles; fiscal space; foreign debt; income inequality